JENNI AI EN EL APRENDIZAJE AUTÓNOMO DE LOS ESTUDIANTES DE LA CARRERA DE EDUCACIÓN BÁSICA DE LA UNIVERSIDAD TÉCNICA DE BABAHOYO, PERÍODO ACADÉMICO ABRIL-AGOSTO 2024. - ARICHABALA ESPINOZA MISAEL DIEGO (2024)
Artificial intelligence is growing exponentially, and its application in education is becoming increasingly important, this article focuses on analyzing the impact of a specific AI system called “JENNI” to improve the autonomous learning of students in the Basic Education career at the Technical University of Babahoyo during the academic period from April to August 2024. It explores how students interact with Jenny and its impact on motivational skills and self-regulation that are fundamental in the digital world. The research will be descriptive and explanatory, focused on understanding how Jenni AI is used in the autonomous learning of Basic Education students and the results obtained. It will use a mixed approach combining qualitative and quantitative data to obtain a complete understanding of the phenomenon. Numerical data will identify the results of using Jenni AI, while qualitative data will provide a detailed and contextualized understanding. In addition, the documentary research will be based on the collection and analysis of existing information in books, articles and reports, which is essential to support the data and obtain reliable results on the incidence of Jenni AI in the autonomous learning of students in the Basic Education career of the Technical University of Babahoyo.